Regulation of inflammatory cytokines and activation of PI3K/Akt pathway by Yiqi Jiedu Formula in recurrent Herpes Simplex Keratitis: Experimental and network pharmacology evidence - Shuyu Xiao; Wanhong Miao; Leilei Wang; Lei Wang; Sisi Tang; Huihui Xu; Ying Yu (Virus Research)
Objective: This study investigates the therapeutic effects of the Yiqi Jiedu (YQJD) formula on Herpes Simplex Keratitis (HSK) induced by herpes simplex virus type 1 (HSV-1) and elucidates its mechanisms of action through experimental and network pharmacology approaches. Methods: Active ingredients of the YQJD formula were identified using UPLC-HRMS. Network pharmacology was employed to predict shared targets between YQJD and HSK, focusing on the PI3K/Akt signaling pathway. Molecular docking was performed to assess the interaction between key ingredients and targets. In vivo, an HSK mouse model was used to evaluate the YQJD formula's impact on corneal lesions and inflammatory factors. In vitro, human corneal epithelial cells (HCECs) were infected with HSV-1 to assess the formula's effect on IL-4 expression. Results: UPLC-HRMS identified 34 compounds in YQJD, with Isovitexin and Formononetin exhibiting high oral bioavailability. Network analysis revealed 97 intersecting targets, implicating the PI3K/Akt pathway in YQJD's mechanism. Molecular docking showed strong affinities between IL-4, IL-6, and YQJD compounds. In vivo, YQJD significantly improved corneal lesions and modulated the expression of IL-4, IL-6, and AKT. In vitro, YQJD-containing serum regulated IL-4 expression in HCECs post-HSV-1 infection. Conclusion: The YQJD formula ameliorates Herpes Simplex Keratitis by regulating inflammatory cytokines and activating the PI3K/Akt pathway, offering a potential therapeutic strategy for HSK.